SISTEM INFORMASI AKUNTANSI PERENCANAAN ANGGARAN BIAYA KONTRUKSI PADA CV. TEGUH SEJAHTERA DENGAN METODE ACTIVITY BASED BUDGETING TAHUN 2023 - Octavian Endra Saputra; Dendy Kurniawan (CV. Denasya Smart Publisher, 2024)
A construction cost budget is needed to calculate a building or project with the costs required for materials and wages, as well as other costs related to the implementation of the building or project. CV Company. TEGUH SEJAHTERA is a company operating in the construction services sector. CV. TEGUH SEJAHTERA has handled various projects ranging from irrigation construction, buildings, roads, bridges, docks, and other construction services. Activity Based Budgeting is a budget preparation process that focuses on improving the system used by the organization in order to produce value for customers and focuses on processes that are integral to an organization, as well as being a process of planning and controlling activities expected by the organization to achieve the budget. that is cost-effective and meets workloads in line with organizational goals and strategies. Using the Activity Based Budgeting method can help solve problems in planning budget costs on CV. TEGUH PROSPEROUS Kendal.